Are College Students’ Attitudes Related to Their Application of Sanctions for Campus Sexual Assault Cases? - Chahal, Jaspreet K. (Journal of interpersonal violence, 2022)
With growing attention to adjudication of campus sexual assault cases, more is known regarding students? views of sexual assault, but little the literature focuses on how students perceive ?justice? in terms of assigning sanctions or guilt/responsibility for such cases. The present study focused on understanding whether college students? preformed attitudes and beliefs were associated with the severity of sanctions they applied across a range of sexual assault cases as well as their assignments of guilt and responsibility to the parties involved. To determine students? attitudes and beliefs mediating effects on sanction choices, five scales (i.e., rape myth acceptance, downplaying the severity of rape, sexism, just world beliefs, and right-wing authoritarianism) were adapted and used for this project. College students (n?=?846) responded to one of four versions of a randomly distributed survey each containing eight vignettes varied to represent levels of 14 factors employed because of their relevance to campus sexual assault cases. Across all versions, sexism was associated with increased responsibility given to the victim. In addition, stronger endorsement of both downplaying significance of rape and rape myth acceptance scales were associated with giving a milder sanction to the perpetrator and increased responsibility and guilt assigned to the victim. Just world beliefs and right-wing authoritarianism associations were inconsistent across the four versions, suggesting these beliefs were situation-specific. Preformed attitudes that are more directly related to the context of sexual assault influenced the designation of sanctions applied to perpetrators and perceptions of guilt and responsibility. Findings are discussed in terms of implications for research and prevention programming.